Syntaxonomy and ecology of forest vegetation in the Štiavnické vrchy Mts (Central Slovakia) - Michal Slezák; Katarína Hegedüšová; Dušan Senko (Acta Societatis Botanicorum Poloniae, 2011)
Vegetation of deciduous forests in the Štiavnické vrchy Mts (Central Slovakia) was studied using the standard Zürich-Montpellier approach. The numerical classification and ordination technique were applied to determine the main forest vegetation types and to find the responsible environmental drivers related to their distribution patterns, respectively. The data set including 198 relevés collected by authors in 1997-2009 and 185 relevés excerpted from literature was used to analysis. Numerical classification resulted in delimitation of fourteen vegetation types representing eleven associations with two variants and two communities within the Quercetea robori-petraeae and Querco-Fagetea classes. The major environmental gradients in variation of forest species composition were associated with moisture and nutrient content following the average Ellenberg indicator values. Along the moisture gradient, vegetation types were ordered from subxerophilous oak forests turn mesophilous mixed oak-hornbeam, beech and ravine forests to hygrophilous riparian alder forest. The results confirmed important role of soil nutrients and moisture by determination of forest vegetation in subcontinental part of Central Europe. Special attention was given to the discussion of floristical characteristics, site conditions and syntaxonomy.